Pengaruh Model Problem-Based Learning Berbantuan Zep Quiz terhadap Kemampuan Berpikir Kritis Siswa pada Materi Ekosistem - Fadillah Turrahmah; Puji Prastowo (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
This research is motivated by the low critical thinking ability of students in Ecosystem material due to teacher-centered learning and the lack of use of interactive media. The purpose of this study is to determine the critical thinking ability of students taught using the Problem Based Learning (PBL) model assisted by Zep Quiz media and its influence on the critical thinking ability of class X students of SMA Negeri 1 Percut Sei Tuan in the 2025/2026 Academic Year. This research is a quantitative study with a quasi-experimental method using a pretest-posttest control group design. The research sample was selected through cluster random sampling. The critical thinking ability instrument was in the form of 10 essay questions. Data were analyzed using the Independent Sample t-test. The results showed that students' critical thinking ability in the PBL class assisted by Zep Quiz (70.7 ± 7.33) was higher than the PBL class without Zep Quiz (65.6 ± 8.79). The results of the hypothesis test showed a significance value of 0.01 (<0.05), so the use of the PBL model assisted by Zep Quiz media had a significant effect on students' critical thinking skills in the Ecosystem material. Zep Quiz media effectively supports the use of PBL in improving students' critical thinking skills.